Prevalence and determinants of insecticide-treated net ownership among women of reproductive age in Nigeria: a mixed-effect insight from the 2021 malaria indicator survey - Oluwakemi Christie Ogidan; Chimezie Igwegbe Nzoputam; Amadou Barrow; Michael Ekholuenetale (Malaria Journal)
Abstract Background Malaria continues to be a significant public health issue in Nigeria, which bears the highest burden of the disease globally. This study examined the prevalence and determinants of insecticide-treated net (ITN) ownership among women of reproductive age in Nigeria. Methods The individual woman questionnaire data from the 2021 Nigeria Malaria Indicator Survey (NMIS) was used. In total, 14,476 women of reproductive age (15–49 years) made up the study's sample that was analysed. The outcome variable in the study was ITN ownership. Percentage and multivariable multilevel binary logistic regression model were estimated at p < 0.05. Results The weighted prevalence of ITN ownership was 62.6% (95% CI 60.6–64.7%). Women aged 25–34 and 35–49 had 12% (aOR = 0.88; 95% CI 0.78–0.98) and 16% (aOR = 0.84; 95% CI 0.74–0.97) reduction in ITN ownership, when compared with women aged 15–24 years. Women who had 1–2 (aOR = 1.13; 95% CI 1.00–1.28), 3–4 (aOR = 1.28; 95% CI 1.11–1.46) and 5 and above living children (aOR = 1.35; 95% CI 1.15–1.58), had higher odds of ITN ownership when compared with those with no living child respectively. Women from non-poor households had higher odds of ITN ownership, when compared with their poor counterparts (aOR = 1.30; 95% CI 1.14–1.49). Women from North East (aOR = 4.52; 95% CI 3.08–6.63) and North West (aOR = 4.18; 95% CI 2.90–6.01) had higher odds of ITN ownership, while those from South East (aOR = 0.40; 95% CI 0.26–0.62) and South South (aOR = 0.59; 95% CI 0.41–0.85) had reductions in the odds of ITN ownership, when compared with women from North Central respectively. Conclusion Approximately two-third of Nigerian women reported ITN ownership. This underscore the need for targeted interventions to address barriers and improve ITN access. While free ITN distribution programmes have been effective, socioeconomic and demographic factors have remained contributory to ITN access. Enhanced strategies should focus on equitable distribution and improved access to ITN among groups to achieve better malaria control outcomes in Nigeria.